مشيخة العرب بالزاب والصحراء الشرقية بين سلطة البايلك العثماني والإدارة الاستعمارية الفرنسية - كحول, عباس; بوقادوم, حمزة (جامعة الوادي - University of Eloued, 2022)
إن البحث في قضية علاقة السلط الدينية والزمنية على غرار شيوخ القبائل ومشايخ شيوخ الطرق الصوفية والزوايا والربط والأشراف والعائلات العريقة المتنفذة بالأنظمة القائمة كالسلطة التركية من جهة والإدارة الفرنسية الاستعمارية من ناحية أخرى، يقودنا إلى الوقوف على إستراتيجية هذه الأطراف لتوظيف هذه القوى الزمنية والدينية، إما للمحافظة على الأوضاع القائمة أو استغلال صراع وتنافس هذه القوى لإخضاعها بالنياشين والقهر؛ وذلك بالعزف على وتر الامتيازات والمكاسب والإعفاءات الضريبية... ومن هذه القوى التي انتقلت من الولاء للسلطة والبايلك العثماني إلى خدمة الإدارة الفرنسية الاستعمارية، نجد مشيخة العرب بالزاب والصحراء الشرقية التي تناوب عليها عائلة آل بوعكاز وعائلة آل بن قانة ... من القرن الخامس عشر ميلادي إلى منتصف القرن التاسع عشر ميلادي، والتي تعد أهم سلطة قبلية سياسية بالمنطقة بالمقارنة مع القوى السياسية والعسكرية والاقتصادية الأخرى كالحنانشة وأولاد مقران وبني جلاب. Research on the issue of relationships of religious and temporal authorities, such as tribal elders, ancient Sufis, zaouias, liaison, supervision and the ancient and influential families of Turkish authority on the one hand and the French colonial administration on the other hand, lead us to discover the strategy of these parties to employ these temporal and religious forces, either by maintaining the conditions of the list, or by exploiting the struggle and the competition of these powers to submit them to appeals and to oppression, by playing the agreement of privileges, gains and exemptions, and of these powers and positions which have passed from the service of power and the Ottoman Beylik to the service of the French administration, we find the sheikh Arabs of Zab and the Eastern Desert, on which alternate the Al-Bu akaz family and the Al-ben gana family, its history extends from the 15th century to the mid19th century, which is the tr the most important political ibal in the region compared to other political, military and economic forces such as Al-Hanansha, Ollad Mukran and Beni Jellab.
مقال
Keywords: مشيخة العرب، الزاب، الصحراء الشرقية، السلطة العثمانية، الإدارة الفرنسية الاستعمارية; sheikh of the Arabs, Zab, eastern desert, Ottoman authority, French colonial administration